1989
DOI: 10.1002/j.1552-4604.1989.tb03272.x
|View full text |Cite
|
Sign up to set email alerts
|

Meptazinol and Morphine in Postoperative Pain Assessed with a New Method for Onset and Duration

Abstract: Meptazinol, m-(3-ethyl-1-methyl-hexahydro-1-H-azepin-3-yl) phenol hydrochloride is a centrally active opioid analgesic with a specificity for the mu-1 receptor. It has been reported to lack many of the side effects commonly observed with morphine and morphinelike drugs in man. The objective of this study was to assess the analgesic efficacy and safety of meptazinol (50 mg and 100 mg) relative to morphine (5 mg and 10 mg) when administered intramuscularly for the treatment of postoperative pain. In addition, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…Stringent criteria such as "a lot" of relief or "complete" relief appeared inappropriate for studies in some pain models, such as dental surgery, where barely 50% of patients ever reach "pain half gone" after receiving 650 mg of aspirin. Therefore, we concurred with Siegel et al 18 in viewing intermediate levels of relief, attainable by most patients treated with OTC analgesics, as most fitting. Of the most commonly used pain relief descriptors-none, a little, some, a lot, or complete relief-"some" fits this description, as does the standard question, "Is your pain half gone?"…”
Section: Criteria For Onsetsupporting
confidence: 89%
See 1 more Smart Citation
“…Stringent criteria such as "a lot" of relief or "complete" relief appeared inappropriate for studies in some pain models, such as dental surgery, where barely 50% of patients ever reach "pain half gone" after receiving 650 mg of aspirin. Therefore, we concurred with Siegel et al 18 in viewing intermediate levels of relief, attainable by most patients treated with OTC analgesics, as most fitting. Of the most commonly used pain relief descriptors-none, a little, some, a lot, or complete relief-"some" fits this description, as does the standard question, "Is your pain half gone?"…”
Section: Criteria For Onsetsupporting
confidence: 89%
“…Others advocate an intermediate level of relief, such as "some" relief or "pain half gone," while another group supports a higher standard (as is frequently used in headache clinical trials) of nearly "complete relief." Preliminary observations 18 suggested that minimal criteria such as "first perceptible," "any," or "slight" relief provide little separation between known analgesics and placebo because most patients report this change quickly after a dose of study medication. Stringent criteria such as "a lot" of relief or "complete" relief appeared inappropriate for studies in some pain models, such as dental surgery, where barely 50% of patients ever reach "pain half gone" after receiving 650 mg of aspirin.…”
Section: Criteria For Onsetmentioning
confidence: 99%
“…The primary efficacy variable was time to analgesia onset measured by the double-click stopwatch method developed by Siegel and colleagues. 12 This method is used to record the onset of analgesia objectively. It distinguishes between a sensation of perceptible pain relief (PPR) and the experience of meaningful pain relief (MPR) by recording the first onset of each with a different stopwatch.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, studies often present conflicting results; some show a strong correlation between ibuprofen plasma concentrations and analgesia (15,24), whereas others show no correlation (27). Attempts to correlate analgesic efficacy with pharmacokinetic parameters are made difficult by the plethora of efficacy endpoints that have been used in studies (Table 1) (25,28–31).…”
Section: Introductionmentioning
confidence: 99%